The Impact of Social Media on Language Proficiency and Writing Skills in Uzbekistan - Juraeva. G. N; Yoqubjonova. D. U. (Development in Language Studies, 2025)
Social media has revolutionized the way people communicate, learn, and express themselves in written and spoken language. This paper explores the impact of social media on language proficiency and writing skills, analyzing both its benefits and challenges. While social media provides increased exposure to diverse linguistic inputs, enhances communication skills, and fosters creativity, it also contributes to the decline of formal writing, grammatical inaccuracies, and dependency on informal expressions. The study highlights the role of social media in shaping digital literacy, the effects of code-switching, and the influence of platform-specific language conventions. Future recommendations emphasize the importance of integrating social media into language education while promoting structured writing and linguistic accuracy. This paper is based on a literature review and theoretical analysis. Recommendations include integrating social media into language education while promoting structured writing practices and improving digital literacy.